Equal (Re-)Distribution of Land as Promotor of Social Justice and Political Loyalty in the Republic of Estonia After WW I - Marju Luts-Sootak; Triinu Rennu; Karin Visnapuu (Právněhistorické studie)
The issue of land redistribution had become the most critical issue in society when the independence of the Estonian Republic was declared in 1918. Land was the primary source of livelihood at that time, and unfairly for Estonians, most of it belonged to Baltic German landlords. Estonians wanted to be masters of their land and cultivate it. To satisfy the “land hunger”, the land of the manors was expropriated and distributed to the peasants. At the same time, it was considered necessary for everyone to get the land as equally as possible. Secondly, the economic aspect was also important: the size of the land had to ensure the family’s economic livelihood. Estonians’ experiences managing things at the local municipality level and the already well-implemented land registry system contributed to the fact that changes in land use and ownership relationships took place quite smoothly, but still not without litigation. Belief in the functioning of the rule of law was confirmed in the administrative court, which checked the legality of land distribution in case of complaints.